الجزء الأول في المدرسة العالية يوسف عبدالستار (Prof. Dr. Eckehard Schulz)،تحليل تعلم كتاب "العربية المعاصرة" لمؤلفه الأستاذ الدكتور إيكينهارد شولتز - Rizki Alfialnsyah, Muhammad; Suparmanto; Nasikin, Muh; Yahya Husaini, Sudi (Cordova Journal language and culture studies, 2025)
This study aims to analyze the use of the Arabic learning book Al-‘Arabiyyah Al-Mu‘āṣirah Part I, written by Prof. Dr. Eckehard Schulz, as a teaching material in Arabic language instruction at Madrasah Aliyah Yusuf Abdussatar Kediri. This research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings show that the book has a systematic structure, communication-based approach, and contains vocabulary and dialogues relevant to students' daily lives. The use of this book has proven effective in improving students’ basic Arabic skills, particularly in vocabulary (mufradāt) and conversation (muḥādathah). However, some challenges were also identified, including limited teaching time, varying student language proficiency levels, and a lack of supporting media. It can be concluded that Al-‘Arabiyyah Al-Mu‘āṣirah is a suitable and beneficial teaching resource for Madrasah Aliyah students, provided it is supported by appropriate teaching strategies and adequate learning tools.